An on-surface reaction confined within a porous molecular template - Judd, Chris J.; Champness, Neil R.; Saywell, Alexander (Wiley-VCH Verlag, 2018)
On-surface reactions based on metal-catalysed Ullmann coupling have been successfully employed to synthesise a wide variety of covalently coupled structures. Substrate chemistry and topology are both known to effect the progression of an on-surface reaction; offering routes to control efficiency and selectivity. Here, we detail ultra-high vacuum scanning probe microscopy experiments showing that templating a catalytically active surface, via a supramolecular template, influences the reaction pathway of an onsurface Ullmann-type coupling reaction by inhibiting one potential intermediate structure and stabilising another.